Prosthesis: From Grammar to Medicine in the Earliest History of the Word - Hawk, Brandon W. (Disability Studies Quarterly, 2018)
This article provides an examination of the earliest history of the term prosthesis in English, re-evaluating other such histories with previously unrecognized archival material from early printed books. These sources include sixteenth- and seventeenth-century early printed books such as handbooks of grammar, English dictionaries, British Latin dictionaries, and medical treatises on surgery. Such an investigation reveals both a more nuanced trajectory of the early history of the word in English and fuller context for a shift in meaning from usages in the study of grammar and rhetoric to the study of medicine and surgery. This narrative, then, speaks to the growth of medical knowledge and discourse in the sixteenth and seventeenth centuries, as well as concepts about disability that remain part of disability studies even in the present field.